Expression and interpretation of relative risk and odds ratio in biomedical research studies - Sharma, Suresh Kumar; Mudgal, Shiv Kumar; Chaturvedi, Jitender (Indian Journal of Community Health, 2020)
Relative risk and odds ratio are commonly used in the biomedical research studies; however, expression and interpretation must be done very carefully. A risk ratio and an odds ratio are used in cohort studies but only odds ratio is used in case control studies. However, relative risk or risk ratio is found to be frequently used in the interventional biomedical research studies. The relative risk and odds ratio provide important information regarding the effect of a risk factor on the outcome of interest. The relative risk and odds ratio of 1 suggests that there is no difference between two groups. A value >1 suggests increase risk, while a value <1 suggest reduction of risk. If the confidence interval meets or includes value 1.00 (line of no difference) indicates there is no difference between the groups.